Gasoline demand and tax salience in Brazil - Sato, João Vitor Tsuyoshi (2020)
Gasoline is one of the main fuels for vehicles in Brazil and being a fossil fuel, is also one of the main responsible for global warming. In this sense, this dissertation makes a study on demand for gasoline in Brazil using a two-stage least square regression. It was observed that when using gasoline taxes as instrumental variables, they tend to increase the value of the gasoline price elasticity, which generates overestimated and generally implausible values. To circumvent this problem, leads and lags were added to the gasoline taxes, since the anticipatory behavior of consumers produces an endogeneity problem and ends up invalidating the regression by instrumental variables. The results demonstrates that the Brazilian consumer has an anticipatory behavior in the face of increases in gasoline taxes. To analyze the extent to which gasoline consumption is affected when its price changes due to market pricing factors or through government taxation, we estimated via ordinary least squares the elasticity-price and elasticity-tax of gasoline in the period from January 2002 to December 2018. This analysis is important since the consumption of fossil fuels is one of the main causes of global warming. The results showed that the Brazilian consumer reacts more to increases in gasoline taxes than increases in market prices for this gasoline. This result is important because it enables greater efficiency in the introduction of public policies that aim to reduce greenhouse gases. Keywords: Gasoline. Demand. Salience. Elasticities. Carbon Emissions.